Effect of SAQ Training and Circuit Resistance Training on Selected Bio Motor and Skill Performance Variables of Football Players - Mr.B.Andrew, Dr.A.Mahaboobjan. Dr.V.Sowmiya, Mr.A.Robinson, Mr.M.Sankar (South Eastern European Journal of Public Health, 2025)
This study was designed to investigate the effect of saq training and circuit resistance training on selected bio motor and skill performance variables of football players. To achieve the purpose of the study (N=60) sixty men football players were selected from affiliated colleges of Periyar University, Salem, Tamilnadu, India as subjects. The age of the subjects ranged from 18 to 25 years. The selected subjects were divided into three equal groups (N=20). Group I underwent SAQ training. Group II underwent circuit resistance training. Group III acted as control group who did not undergo any specialized training program other than their daily routine. The bio motor variables such as explosive power, cardio respiratory endurance and muscular endurance; and the performance variable such as passing and shooting were selected as dependent variables and they bio motor variable were assessed by vertical jump, cooper 12 minutes run and walk and sit ups test ; and performance variable assessed by Mor – Christian Football Ability Test . The subjects were concerned with their particular training programmes for three sessions per week for twelve weeks, alternatively three days per week. The collected data from three groups prior to and immediately after the training programme on selected criterion variables were statistically analyzed with analysis of covariance (ANCOVA). The result of the study reveals that the SAQ training and circuit resistance training groups achieved significant improvement on selected bio motor variables such as explosive power, cardio respiratory endurance and muscular endurance and the performance variable such as passing and shooting of college men football players.